Mesogenic Schiff base esters with terminal chloro group: Synthesis, thermotropic properties and X-ray diffraction studies - Ha, Sie-Tiong; Ong, Lay-Khoon; Sivasothy, Y.; Yeap, Guan-Yeow; Lin, Hong-Cheu; Lee, Siew-Ling; Boey, Peng-Lim; Bonde, N.L. (Academic Journals, 2010)
A new homologous series of Schiff base esters comprising a terminal chloro substituent was studied. The chloro substituent contributes to the molecular polarizability, thus, affecting intermolecular interactions, hence, resulting in smectic polymorphism. The mesomorphic properties were studied using differential scanning calorimetry, polarizing optical microscopy and temperature-dependent X-ray diffractometry. Whilst the n-pentanoyloxy and n-heptanoyloxy derivatives exhibited enantiotropic smectogenic A and B phases, monotropic smectogenic A and B phases were observed in the n-butanoyloxy and n-hexanoyloxy derivatives. Enantiotropic smectogenic A and monotropic smectogenic B phases were observed in the n-octanoyloxy to n-hexadecanoyloxy derivatives. The highest member of this series, the n-octadecanoyloxy derivative, exhibited an enantiotropic smectogen A phase. The homologous members were compared with structurally related series to establish their chemical structure-mesomorphic behavior relationships.